Choice of ownership structure and firm performance: Evidence from Estonia - Derek C. Jones; Panu Kalmi; Niels Mygind (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
In this paper we use rich panel data for a representative sample of Estonian enterprises to analyse diverse issues related to the determinants of ownership structures and ownership changes after privatisation.A key focus is to determine whether ownership changes are related to economic efficiency.While employee owned firms are found to be much more prone than other firms to switch ownership categories, often "employee owned" firms remain "insider-owned" as ownership passes from current employees to managers and former employees.Logit analyses of the determinants of ownership structures and ownership changes provides mixed support for several hypotheses.As predicted: (i) wealth and resource constraints play a crucial role in the determination of ownership, with foreigners buying firms with the highest equity levels and insiders buying firms with the lowest equity valuations; (ii) risk aversion explains subsequent ownership changes, especially away from employee ownership; (iii) allocation of ownership depends on the pre-privatisation origin and location of the firm, and these factors also influence subsequent ownership changes.Finally we compare our findings with those achieved by using more conventional approaches to analyze efficiency that use very similar data.Reassuringly the evidence presented in this paper is consistent with the view that efficiency considerations drive ownership changes (while earlier analysis for Estonia and for many other transition economies has identified the impact of ownership on economic performance.)However, the findings in this paper also establish that there are important influences besides economic efficiency that affect enterprise ownership and ownership changes.
URN:NBN:fi:bof-201408071943
Keywords: G3; J5; P2; P3; 330; Privatisation; ownership change; employee ownership; transition economies; Estonia